16S rRNA Gene Amplicon Sequence Data from Feces of Wild Deer (Cervus nippon) in Japan - Ishida-Kuroki, Kasumi; Takeshita, Nachiko; Nitta, Yoshihiro; Chuma, Takehisa; Maeda, Ken; Shimoda, Hiroshi; Takano, Ai; Sekizaki, Tsutomu (Microbiology resource announcements, 2020)
We report 16S rRNA amplicon sequence data from feces of 109 wild deer in Japan. The dominant bacterial taxa in fecal microbiota of wild deer hunted between village and mountainous areas and those living on Miyajima Island and in Nara Park were similar but differed in abundance. We report 16S rRNA amplicon sequence data from feces of 109 wild deer in Japan. The dominant bacterial taxa in fecal microbiota of wild deer hunted between village and mountainous areas and those living on Miyajima Island and in Nara Park were similar but differed in abundance.